Pengaruh Faktor Fisik, Sosial dan Psikologis Terhadap Kepuasan Kerja Karyawan PT. Ade Pas Palembang - Al Fathur, Khaliq; Trihandayani, Zaleha; Masdaini, Efrina (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
This study aims to determine the influence of physical, social and psychological factors on employee job satisfaction at PT. Ade Pas Palembang. The population in this study was 136 permanent employees and the sample taken was 102 employees. Sampling used the Proportionate Stratified Random Sampling Technique. The type of research used is associative research. The data required in this study are primary data and secondary data. The data collection method used is a questionnaire. Data analysis uses quantitative qualitative data analysis. The analysis technique used in this study is multiple linear regression analysis. The results of the hypothesis test show that simultaneously/together Physical, Social and Psychological Factors have a positive effect on Employee Job Satisfaction. While partially Physical, Social and Psychological Factors have a positive effect on Employee Job Satisfaction. Social Factors have a positive effect on Employee Job Satisfaction. Psychological Factors have a positive effect on Employee Job Satisfaction. The results of the determination coefficient show that the contribution of physical, social and psychological factors to employee job satisfaction at PT. Ade Pas Palembang is 58.7%